Iron Metabolism in Ferroptosis - Chen, Xin; Yu, Chunhua; Kang, Rui; Tang, Daolin (Frontiers in cell and developmental biology, 2020)
Ferroptosis is a form of regulated cell death that is characterized by iron-dependent oxidative damage and subsequent plasma membrane ruptures and the release of damage-associated molecular patterns. Due to the role of iron in mediating the production of reactive oxygen species and enzyme activity in lipid peroxidation, ferroptosis is strictly controlled by regulators involved in many aspects of iron metabolism, such as iron uptake, storage, utilization, and efflux. Translational and transcriptional regulation of iron homeostasis provide an integrated network to determine the sensitivity of ferroptosis. Impaired ferroptosis is implicated in various iron-related pathological conditions or diseases, such as cancer, neurodegenerative diseases, and ischemia-reperfusion injury. Understanding the molecular mechanisms underlying the regulation of iron metabolism during ferroptosis may provide effective strategies for the treatment of ferroptosis-associated diseases. Indeed, iron chelators effectively prevent the occurrence of ferroptosis, which may provide new approaches for the treatment of iron-related disorders. In this review, we summarize recent advances in the theoretical modeling of iron-dependent ferroptosis, and highlight the therapeutic implications of iron chelators in diseases.Ferroptosis is a form of regulated cell death that is characterized by iron-dependent oxidative damage and subsequent plasma membrane ruptures and the release of damage-associated molecular patterns. Due to the role of iron in mediating the production of reactive oxygen species and enzyme activity in lipid peroxidation, ferroptosis is strictly controlled by regulators involved in many aspects of iron metabolism, such as iron uptake, storage, utilization, and efflux. Translational and transcriptional regulation of iron homeostasis provide an integrated network to determine the sensitivity of ferroptosis. Impaired ferroptosis is implicated in various iron-related pathological conditions or diseases, such as cancer, neurodegenerative diseases, and ischemia-reperfusion injury. Understanding the molecular mechanisms underlying the regulation of iron metabolism during ferroptosis may provide effective strategies for the treatment of ferroptosis-associated diseases. Indeed, iron chelators effectively prevent the occurrence of ferroptosis, which may provide new approaches for the treatment of iron-related disorders. In this review, we summarize recent advances in the theoretical modeling of iron-dependent ferroptosis, and highlight the therapeutic implications of iron chelators in diseases.